Probing interaction of Gram-positive and Gram-negative bacterial cells with ZnO nanorods - Jain, Aanchal; Bhargava, Richa; Poddar, Pankaj (Materials Science & Engineering C-Materials for Biological Applications, 2013)
In the present work, the physiological effects of the ZnO nanorods on the Gram positive (Staphylococcus aureus and Bacillus subtilis) and Gram-negative (Escherichia coli and Aerobacter aerogenes) bacterial cells have been studied. The analysis of bacterial growth curves for various concentrations of ZnO nanorods indicates that Gram positive and Gram negative bacterial cells show inhibition at concentrations of similar to 64 and similar to 256 mu g/mL respectively. The marked difference in susceptibility towards nanorods was also validated by spread plate and disk diffusion methods. In addition, the scanning electron micrographs show a clear damage to the cells via changed morphology of the cells from rod to coccoid etc. The confocal optical microscopy images of these cells also demonstrate the reduction in live cell count in the presence of ZnO nanorods. These, results clearly indicate that the antibacterial activity of ZnO nanorods is higher towards Gram positive bacterium than Gram negative bacterium which indicates that the structure of the cell wall might play a major role in the interaction with nanostructured materials and shows high sensitivity to the particle concentration. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Confocal; Growth curve; Nanorods; SEM; Zeta potential; ZnO